Clothing and cultural identity between belonging and alienation, an anthropological vision (Journal of the College of Basic Education, 2022)
Fashion is one of the aspects that people live in, and there is no doubt that it constitutes another aspect in which the suffering of peoples is sought from the other hand.Clothing is considered one of the most important elements of material culture that determines - at least outwardly - the individual's belonging to a particular cultural or ethnic group, and this is clearly reflected in the huge diversity of materials used in making clothes, a diversity usually associated with the diversity of the geographical environments in which a person lives, as well as It is reflected in the diversity of colors and styles that the system of prevailing cultural values plays a major role in testingThis study is an attempt as much as possible to find out the development of fashion in Iraq, and it is a scientific study in which the local, religious and geographical character is taken into account, and it is also taken into account that it is accurate so that it does not accommodate for speculation.